SUB1 has photoreceptor dependent and independent functions in sexual development and secondary metabolism in Trichoderma reesei. Issue 5 (22nd October 2017) - Bazafkan, Hoda; Beier, Sabrina; Stappler, Eva; Böhmdorfer, Stefan; Oberlerchner, Josua T.; Sulyok, Michael; Schmoll, Monika
Summary: Light dependent processes are involved in the regulation of growth, development and enzyme production in Trichoderma reesei . The photoreceptors BLR1, BLR2 and ENV1 exert crucial functions in these processes. We analyzed the involvement of the transcription factor SUB1 in sexual development as well as secondary metabolism and its position in the light signaling cascade. SUB1 influences growth and in contrast to its homologue in N. crassa, SUB1 is not essential for fruiting body formation and male fertility in T. reesei, but required for female fertility. Accordingly, SUB1 is involved in the regulation of the pheromone system of T. reesei . Female sterility of mutants lacking env1 is rescued in triple mutants of blr1, blr2 and env1, but not in double mutants of these genes. Confrontation of strains lacking sub1 results in growth arrest prior to contact of the potential mating partners. This effect is at least in part due to altered secondary metabolite production. Additionally, together with BLR1 and BLR2, SUB1 is essential for spore pigmentation and transcription of pks4, and secondary metabolism is regulated by SUB1 in a light‐ and nutrient dependent manner. Our results hence indicate rewiring of several pathways targeted by SUB1 in T. reesei . Abstract : T. reesei SUB1 has photoreceptor dependent and independent functions in the regulation of growth, sexual development and secondary metabolism in T. reesei . Compared to other filamentous fungi, rewiring of the SUB1 regulatory pathway was observed for functions in fertility and secondary metabolism and for some functions in its position in the light signaling cascade.